Evidence for the Essential Arginine and Histidine Residues in Catalytic Activity of Glucose 6-Phosphate Dehydrogenase from Streptomyces aureofaciens (Journal of Sciences, Islamic Republic of Iran)
Glucose 6-phosphate dehydrogenase (G6PD) was purified from Streptomyces aureofaciens and inactivated with butanedione and diethylpyrocarbonate. Incubation of the enzyme with butanedione resulted in a rapid activity loss (80%) within 5 min, followed by a slow phase using a molar ratio to enzyme concentration of 100. Fluorescence studies showed a conformational change in the butanedione-modified enzyme. NAD+, NADP+ and glucose 6-phosphate protected the enzyme against inactivation. Diethylpyrocarbonate (2 mM) completely inactivated the enzyme after 2 min. Stoichiometry of the inactivation showed 2 moles of histidine residues per mole of enzyme with complete activity loss. Maximum emission spectrum of the enzyme decreased (23%) upon modification and the presence of NAD+ or NADP+ further decreased the fluorescence by 27% and 10.5%, respectively. The data suggest that essential arginine and histidine residues may be involved in the catalytic activity of Streptomyces aureofaciens G6PD